2016
DOI: 10.1177/2050313x16675257
|View full text |Cite
|
Sign up to set email alerts
|

A feasible repetitive transcranial magnetic stimulation clinical protocol in migraine prevention

Abstract: Objective:This case series was conducted to determine the clinical feasibility of a repetitive transcranial magnetic stimulation protocol for the prevention of migraine (with and without aura).Methods:Five patients with migraines underwent five repetitive transcranial magnetic stimulation sessions separated in 1- to 2-week intervals for a period of 2 months at a single tertiary medical center. Repetitive transcranial magnetic stimulation was applied to the left motor cortex with 2000 pulses (20 trains with 1s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 16 publications
2
22
0
2
Order By: Relevance
“…Our review identified 18 studies, including eight RCTs (63, 66-68, 70, 74, 76, 79), seven prospective observational studies (64,69,71,72,75,78,80), and three case studies (65,73,77), that evaluated the ability of rTMS to reduce the associated symptoms of headache, including frequency, duration, and severity of headache. The RCTs conducted by Brighina et al (63), Lipton et al (66), and Misra et al (68) showed that outcome migraine measures, including headache frequency, VAS score, headache index, and number of abortive medications, were significantly reduced in patients with migraine who received rTMS treatment (10-20 Hz high-frequency or single-pulse TMS) as compared with those in patients who received sham stimulations.…”
Section: Headachementioning
confidence: 99%
“…Our review identified 18 studies, including eight RCTs (63, 66-68, 70, 74, 76, 79), seven prospective observational studies (64,69,71,72,75,78,80), and three case studies (65,73,77), that evaluated the ability of rTMS to reduce the associated symptoms of headache, including frequency, duration, and severity of headache. The RCTs conducted by Brighina et al (63), Lipton et al (66), and Misra et al (68) showed that outcome migraine measures, including headache frequency, VAS score, headache index, and number of abortive medications, were significantly reduced in patients with migraine who received rTMS treatment (10-20 Hz high-frequency or single-pulse TMS) as compared with those in patients who received sham stimulations.…”
Section: Headachementioning
confidence: 99%
“…53,54 Six of the eight studies examined episodic and chronic sufferers. 51,52,[55][56][57][58][59] One study looked at males only. 59 Even though reports of migraine with aura were included in several studies, the number of experiencers was few, with very small sample sizes, and was not examined exclusively in any studies.…”
Section: Treatment Demographicsmentioning
confidence: 99%
“…53 Pulses per session varied greatly as well, with many studies looking at the lowest amount of 600 per session 51,52,[55][56][57][58] and a couple studies using the highest amount reviewed at 2000 per session. 53,59 Total number of pulses over the entire treatment regimen ranged from 600 51,52,57 at the lowest to 24,000 53 at the highest (see Table 1). The amount of sessions and pulses did not seem to influence treatment tolerance, but the stimulation intensity and demographics of the migraine sufferer may have.…”
Section: Number Of Sessions and Pulsesmentioning
confidence: 99%
“…In chronic headache related to mild posttraumatic head injury (MTHI-H), it has shown ≥50% improvement in pain intensity and frequency in 58.3% of the patients [11]. In migraine, some have reported a reduction of 31.2% in pain frequency and 37.8% in attack duration [70] in two-third of the patients [66]. The acute variant, with or without aura, seems to have a better response than the chronic one [67][68][69][70][71][72].…”
Section: Transcranial Magnetic Stimulation (Tms)mentioning
confidence: 99%
“…In migraine, some have reported a reduction of 31.2% in pain frequency and 37.8% in attack duration [70] in two-third of the patients [66]. The acute variant, with or without aura, seems to have a better response than the chronic one [67][68][69][70][71][72]. There seems to be a cumulative effect, so that the longer this treatment modality is applied, the greater is the attack duration reduction [69].…”
Section: Transcranial Magnetic Stimulation (Tms)mentioning
confidence: 99%